Land Suitability for Rice Growing In the Klang Valley Using Geographical Information System and Analytical Hierarchy Process for Urban Food Security - Abu Bakar, Shamsul (2007)
Klang Valley is the most rapidly growing region in terms of physical and economic development in Malaysia. It has a population of 4.07 million people, accounting for nearly 17.5 % of the total national population. Thus, a large amount of constant food supply is required to meet the population’s demand. However, the current situation is that Klang Valley is heavily dependent on external sources of food supply. In the event of emergencies such as natural or man-made disasters, Klang Valley will face a high risk of disruption in food supply. The aim of this study is to identify and analyze potential rice cultivation areas as urban food reservoir within the highly urbanized Klang Valley. By using Geographical Information System (GIS) and Analytical Hierarchy Process (AHP), a land suitability analysis for rice cultivation was carried out in this study area. To construct a rice suitability model, expert evaluation on criteria such as soil series, rainfall, topography, groundwater and strategic agriculture distances were evaluated based on weightage ranking. Those weightage were obtained by using a Pairwise Comparison Method and then converted into spatial values using ArcGIS 9 weighted overlay process. Results indicated several areas within the Klang Valley having strategic potentials for rice growing. These areas are classified into three major classes - highly suitable, suitable and moderately suitable. The percentage of highly suitable area is 3504.35 ha (8.82 %), suitable areas 18793.28 ha (47.34 %) and moderately suitable areas 17403.02 ha (43.84%). The total areas suitable for rice growing is 39700.65 ha (14%) from the total size of Klang Valley.